2008
DOI: 10.1016/j.ijrefrig.2007.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the transportation and melting of thick ice slurries in pipes

Abstract: This paper presents the results of experiments and modelling carried out on ice slurries flowing in uninsulated steel pipes with a nominal diameter of 50 mm. The slurries used were formed from 4.75% NaCl aqueous solution and had ice mass fractions in the range 18-42%, with a view to the use of thick ice slurry 'pigs' as a pipeline clearing technique. Of particular interest was the distance over which such slurries can survive as plug-like entities, before melting reduces them to ineffective thin two-phase susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…However, ice production, transportation, and storage are expensive, energy-intensive, and poorly scalable. Moreover, because ice melts rapidly when present in small particles, the distance over which an ice slurry may function as an effective pig is severely limited (43,44). This is particularly problematic in industries where most product movement occurs during the summer months (e.g., wine production).…”
Section: Resultsmentioning
confidence: 99%
“…However, ice production, transportation, and storage are expensive, energy-intensive, and poorly scalable. Moreover, because ice melts rapidly when present in small particles, the distance over which an ice slurry may function as an effective pig is severely limited (43,44). This is particularly problematic in industries where most product movement occurs during the summer months (e.g., wine production).…”
Section: Resultsmentioning
confidence: 99%
“…2. The development and validation of predictive tools which can estimate the viable range for the ice pig for prescribed boundary conditions [25]. 3.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Evans [21] identifies the physics limiting the longevity of ice pigs. Evans et al [25] have developed a numerical model that predicts distances ice pigs can be expected to travel as a function of pipe characteristics, ice fraction, and flow velocity. This work shows that the distance a pig can travel as a viable entity increases with increasing speed.…”
Section: Supporting Experimental Work In the Laboratorymentioning
confidence: 99%
“…The critical review by Egolf and Kauffeld [4] and references therein show many previous studies of ice-slurry cold thermal storage systems; the properties studied include velocity profiles, ice-fraction profiles, pressure losses, and heat transfer rates for a variety of flow conditions. After the review by Egolf and Kauffeld, some studies have reported the melting heat transfer of ice-slurry flows through tubes, and correlation equations for melting heat transfer were derived from the results [5][6][7][8]. In addition, some numerical approaches have been exploited to build a heat transfer model for melting of ice slurries [9,10].…”
Section: Pgmentioning
confidence: 99%